Does social distance modulate adults' egocentric biases when reasoning about false beliefs? - Benjamin G Farrar; Ljerka Ostojić (PLoS ONE)
When given privileged information of an object's true location, adults often overestimate the likelihood that a protagonist holding a false belief will search in the correct location for that object. This type of egocentric bias is often labelled the 'curse of knowledge'. Interestingly, the magnitude of this bias may be modulated by the social distance between the perspective taker and target. However, this social distance effect has yet to be fully demonstrated when adults reason about false beliefs. Using a continuous false belief task, we investigated i) whether adults were biased by their own knowledge when reasoning about another's false belief, ii) whether the magnitude of this egocentric bias was modulated by social distance, and iii) whether this social distance effect extended to a heterospecific out-group, namely a dog. To test these hypotheses we conducted three experiments. In Experiment 1 (N = 283), we used an established continuous false belief task, in Experiment 2 (N = 281) we modified this task, and Experiment 3 (N = 744) was a direct replication of Experiment 2. Across these experiments, the curse of knowledge effect was reliably replicated when adults mentalised about an in-group protagonist, and replicated in two of the three studies (Experiments 1 and 3) when adults mentalised about out-group protagonists. In an internal-meta analysis, the curse of knowledge effect was present across all conditions, and there was no effect of social distance. Hence, overall these data are not consistent with the hypothesis that social distance modulates adults' egocentric biases when reasoning about false beliefs. The finding that egocentric biases of a similar magnitude were observed when adults mentalised about an in-group protagonist and a dog suggests that interpersonal dissimilarity is not in itself sufficient to reduce egocentric bias when reasoning about false beliefs.